Analisis Deskriptif Sistem Informasi Manajemen Rumah Sakit Dengan Menggunakan Model For Mandatory Use Of Software Technologies (MMUST) - Darmawan, Mochammad Arief; Permanasari, Adhistya Erna; Sanjaya, Guardian Yoki (Jurnal Sistem Informasi Kesehatan Masyarakat, 2024)
Background: The Hospital Management Information System (HMIS) is a system where the hospital collects and processes all the information needed, processed and collected via computer about health services and management and this information can be interconnected between units within the hospital environment. Hospital Pasirian Lumajang has been using HMIS for about 2 years but until now the use of HMIS is still not optimal. Users are an important aspect to realize the ideal HMIS. The Model for Mandatory Use of Software Technologies (MMUST) is a model for assessing system success in mandatory environments. By understanding user perceptions, appropriate recommendations can be found to maximize the use of HMIS in improving the quality of patient care.Methods: This type of research uses descriptive data analysis with cross-sectional data collection. The research population is all officers who use HMIS. The research instrument is a questionnaire.Results: The quality of information needs to be improved, performance expectations of the system are very high, social influence is also quite good. attitude towards HMIS is quite positive, the intensity of using HMIS is very high. Some users are also on average satisfied with the overall HMIS, and the benefits from the management side are not good because the information produced is still not in accordance with user needs.Conclusions: HMIS implementation is still in its early stages and the benefits of HMIS implementation are still limited, so it is necessary to develop HMIS.